Time efficiency analysis of single floor shophouse construction project using the CPM (Critical Part Method) - Surahman, Surahman; Radityatama, Yosafat Henry; Padillah, Ahmad; Satryawati, Satryawati (Institute of Computer Science (IOCS), 2025)
This study examines the efficiency of the implementation time of a single floor shophouse construction project in Samarinda City, through the application of the Critical Path Method (CPM). Secondary data in the form of a project implementation schedule was analyzed by preparing a work network diagram, calculating Earliest Event Time (EET) and Latest Event Time (LET), and identifying the critical path. The results of the analysis show that the duration of project implementation with normal time reaches 121 days, while with an accelerated scenario (quick time) can be cut to 87 days. The critical path consists of the sequence of activities A (preparation) → B (foundation) → C (structure) → D (wall) → E (roof) → G (harmonica door) → H (bathroom) → I (septic tank) → J (canopy) → K (electrical installation) → L (painting) → M (finishing), so that these activities become the main focus of control to avoid delays. Strategic recommendations include optimizing resource allocation, rescheduling non-critical activities, and implementing fast-track and overlapping work to shorten the implementation duration without compromising construction quality